CREATING THE CORRUPTION COMBATER WARRIORS IN INDONESIA - Abdullah Hehamahua (Program Pascasarjana Universitas Negeri Jakarta, 2014)
The objective of this research was to obtain a comprehensive understanding of what, why, andhow, the programs and performances which ideally need to be directed by integrity andprofessionalism are actually handled by the human resource management in the CorruptionEradication Commission (CEC). The qualitative approach to conduct the case study collectedthe data through a participant observation procedure, and triangulated with interviews withkey informants, document analysis, and recordings. The study found that (1) the planning ofthe human resource, including the recruitment and selection process, has been conducted tofollow the highest standards applied in state institutions and government agencies inIndonesia; (2) CEC is conducting education, training, and development programs of its humanresource to improve organizational performance; (3) CEC is the first state institution orgovernment agency to use performance as the parameter for reward and punishment; (4) CECis the first state institution and government agency to use a merit system in determining thesalary; (5) the values of integrity and professionalism constitute are the basic priciples toguide the corporate culture of the auditors of CEC. The findings indicate the need to improvethe recruitment and selection process, to establish the standards of performance, evaluationjand career management in all the units, and to continue the Coaching, mentoring, andCounceling (CMC) program to maintain integrity and professionalism of the whole body ofthe human resource of the CEC.Keywords: human resource management, performance, integrity, professionalism.